2018
DOI: 10.11591/ijece.v8i1.pp585-595
|View full text |Cite
|
Sign up to set email alerts
|

A Carrierless Amplitude Phase (CAP) Modulation Format: Perspective and Prospect in Optical Transmission System

Abstract: The explosive demand of broadband services nowadays requires data communication systems to have intensive capacity which subsequently increases the need for higher data rate as well. Although implementation of multiple wavelengths channels can be used (e.g. 4 × 25.8 Gb/s for 100 Gb/s connection) for such desired system, it usually leads to cost increment issue which is caused by employment of multiple optical components. Therefore, implementation of advanced modulation format using a single wavelength channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…These filters are the result of the multiplication of a pulse-shaping filter with two orthogonal carriers. The most common pulse-shaping filter is the rootraised-cosine (RRC) function and the impulse response expressions of the two orthogonal CAP filters [23] in the digital domain are:…”
Section: A Carrierless Amplitude Phase Modulationmentioning
confidence: 99%
“…These filters are the result of the multiplication of a pulse-shaping filter with two orthogonal carriers. The most common pulse-shaping filter is the rootraised-cosine (RRC) function and the impulse response expressions of the two orthogonal CAP filters [23] in the digital domain are:…”
Section: A Carrierless Amplitude Phase Modulationmentioning
confidence: 99%
“…Some geometrical coefficients like a thickness of metal and substrate; the hole diameter also the number of periodic holes and metal properties can effect on EOT spectra because the surface plasmons that will be excited by incident light is affected by changing the size of hole and it have been confirmed that any change in the size of the holes lead to a small variations in transmission efficiency and peak [11][12][13][14][15]. Je Hong provided that the transmission characteristics is a function of film thickness of metallic hole array samples which is prepared with different hole periodicity, size and shape on a silica substrate and shows highly transmission efficiency at small thickness of gold metal [16,17].…”
Section: Introductionmentioning
confidence: 98%
“…The fibers are not emitted the transmitted signals without tampering while the copper cable dose, this fiber property preventing the drawing of transmitted signal. The non-linear behavior of optical fiber is its major weakness [11][12][13][14][15][16][17][18][19][20]. This nonlinearity is a directly proportional with the power of the signal been transmitted through the fiber optic.…”
Section: Introductionmentioning
confidence: 99%